Propuesta de un área de recreación turística en el rancho cascada "4 EROS" del cantón Buena Fe, provincia de Los Ríos, 2020 - Velásquez Valdez, Gissela Valeria (2020)
Currently, recreational areas have become instruments that allow the benefit of existing tourism resources, in the attractions or natural areas, contributing to boost the economic growth of communities, distraction of people and tourism development in the sector. In the present investigation, by means of the diagnosis of the present situation, the state of the "4 Eros Waterfall Ranch" was recognized, in which it was possible to be verified the deficiency of tourist facilities that contributes to the visitors' recreation and to identify different species of flora and fauna among them the species in danger of extinction, on the other hand, by means of the application of online surveys it was possible to determine that 98% would agree to implement new tourist facilities in the zone of study. Finally, a design of a tourist recreation area in the "4 Eros" waterfall Ranch was elaborated that will contribute to the socioeconomic growth of the community and will favor the integration of all the inhabitants of the site. Keywords: Tourist area, tourist facilities, design